HUBUNGAN IKLIM ORGANISASI DENGAN KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR DINAS PERINDUSTRIAN, PERDAGANGAN, DAN KOPERASI KABUPATEN BALANGAN - Erna Suriyani (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2015)
This study is intended to determine the relationship of organizational climate with the performance of civil servants in the Department of Industry, Trade and Cooperative Balangan.This type of research conducted in this research is explanatory research, which means the writer wants to examine the relationship of organizational climate with the performance of civil servants.The approach used in this study is the quantitative approach. By using this quantitative method, it will show symptoms that can be measured accurately. This approach will give a meaning in relation to the interpretation of the statistics is not linguistic and cultural significance.The findings in this study indicate that there was a relationship between organizational climate with the performance of civil servants. Climate such organizations as seen from the observance of employees on regulation, organizational climate seen on the protection of employees, organizational climate seen from the award of the boss, organizational climate seen of the presence or absence of unfair competition, organizational climate seen from the opportunity to increase knowledge, and organizational climate views of employee involvement in decision-making through meetings, meetings, regular evaluations or incidental.